A new brachyopid, Batrachosuchus concordi sp. nov. from the Upper Luangwa Valley, Zambia with a redescription of Batrachosuchus browni Broom, 1903 - Chernin, Sharon (Bernard Price Institute for Palaeontological Research, 1977)
Two brachyopid skulls from southern Africa are described: one from the N'tawere Formation, Zambia is assigned to Batrachosuchus concordi sp. nov. and the other, B. browni Broom from the Cynognathus zone of South Africa is used as comparative material after further preparation had been effected on it. Both are assessed in relation to published descriptions of B. watsoni and it is concluded that B. concordi is closest to B. watsoni. The possibility that B. watsoni and B. browni belong to the same species is discounted for the present as there are four distinct differences in their skull morphology. Some poorly preserved and enigmatic bones from immediately behind the occiput of B. concordu are interpreted as limb and girdle elements. Associated with these bones are an axis and an atlas. All three species are at about the same level of organisation and that helps confirm that the Cynognathus zone of South Africa and the N'tawere Formation of Zambia are of approximately the same age and span the Lower-Middle Triassic boundary.
Main article
Keywords: brachyopid; Zambia